O ensino de história nas disciplinas eletivas: uma experiência de educação patrimonial sobre a história antiga da ilha de Upaon-Açu no IEMA Pleno Gonçalves Dias - MORAES, João Pedro da Silva (2024)
This work addresses the teaching of History in elective subjects through the dialogue with educational processes that are part of Heritage Education. It highlights how elective subjects can be a fruitful space for the performance of the History teacher, given the reduction in teaching hours and the devaluation that the subject suffered with the enactment of Law no 13.415/2017. It discusses how dialogical Heritage Education, combined with the teaching of History, effectively contributes to the improvement of pedagogical practices, as well as to a better understanding by students of their socio-cultural universe. Finally, it emphasizes, through the Heritage Education experience carried out at the full-time school IEMA Pleno Gonçalves Dias, that one of the great virtues of working with Heritage Education linked to the teaching of History lies in the consideration and appreciation of the plurality of subjects, the cultural diversity of the various peoples and communities existing in the world, configuring alterity as the guiding principle of this practice. Furthermore, the work includes a didactic guide that integrates Heritage Education and the teaching of History in elective subjects, assisting the teacher in the development of these subjects..